Use of prescribed psychotropic drugs among medical students and associated factors: a cross-sectional study - Fasanella, Nicoli Abrão; Custódio, Clarissa Garcia; Cabo, Júlia Santos do; Andrade, Gabriel Sousa; Almeida, Fernando Antônio de; Pavan, Maria Valéria (São Paulo Medical Journal, 2022)
BACKGROUND: The worldwide prevalences of anxiety and depressive disorders are 3.6% and 4.4%, respectively. Among medical students, many studies have indicated that the prevalences of these mental disorders vary between 19.7% and 47.1%, but there is a lack of information on psychotropic drug usage in this group of students. OBJECTIVE: To evaluate the prevalence of psychotropic drug use, adherence to therapy and main clinical and diagnostic indications relating to psychotropic drug use among medical students. DESIGN AND SETTING: Cross-sectional study at a Brazilian private university in the city of Sorocaba, state of São Paulo. METHODS: Observational analytical cross-sectional study, conducted during the second semester of 2019, through a semi-structured online questionnaire, answered by first to sixth-year medical students. RESULTS: Among the 263 participants (41.7% of the 630 enrolled students), the current prevalence of psychotropic drug usage was 30.4%. This prevalence increased over the course and 90.7% of the drugs were prescribed at regular medical consultations (85.5% by psychiatrists). The main indications for psychotropic drug usage were anxiety (30.0%), depression (22.8%), insomnia (7.2%), panic (5.3%) and att ention deficit hyperactivity disorder (3.8%). Women were more likely to present diagnoses of depression and panic. Most of the participants used antidepressants and had good adherence to medications. Adequate sleep and regular physical activity were identified as protective factors against mental disorders. CONCLUSION: The prevalence of mental disorders among medical students is high, which justifies the use of psychotropic drugs. This study provides valuable information and recommendations for institutional educational actions to improve students’ mental health.